The Natural History of Teneurins: A Billion Years of Evolution in Three Key Steps - Wides, Ron (Frontiers in Neuroscience, 2019)
The entire evolutionary history of the animal gene family, Teneurin, can be summed up in three key steps, plus three salient footnotes. In a shared ancestor of all bilaterians, the first step began with gene fusions that created a protein with an amino-terminal intracellular domain bridged via a single transmembrane helix to extracellular EGF-like domains. This first step was completed with a further gene fusion: an additional carboxy-terminal stretch of about 2000 amino acids (aa) was adopted, as-a-whole, from bacteria. The 2000 aa structure in Teneurin was recently solved in three dimensions. The 2000 aa region appears in a number of bacteria, yet was co-opted solely into Teneurin, and into no other eukaryotic proteins. Outside of bilaterian animals, no Teneurins exist, with a “Monosiga brevicollis caveat” brought below, as ‘the third footnote.” Subsequent to the “urTeneurin’s” genesis-by-fusions, all bilaterians bore a single Teneurin gene, always encoding an extraordinarily conserved Type II transmembrane protein with invariant domain content and order. The second key step was a duplication that led to an exception to singleton Teneurin genomes. A pair of Teneurin paralogs, Ten-a and Ten-m, are found in representatives of all four Arthropod sub-phyla, in: insects, crustaceans, myriapods, and chelicerates. In contrast, in every other protostome species’ genome, including those of all non-Arthropod ecdysozoan phyla, only a single Teneurin gene occurs. The closest, sister, phylum of arthropods, the Onychophorans (velvet worms), bear a singleton Teneurin. Ten-a and Ten-m therefore arose from a duplication in an urArthropod only after Arthropods split from Onychophorans, but before the splits that led to the four Arthropod sub-phyla. The third key step was a quadruplication of Teneurins at the root of vertebrate radiation. Four Teneurin paralogs (Teneurins 1 through 4) arose first by a duplication of a single chordate gene likely leading to one 1/4–type gene, and one 2/3-type gene: the two copies found in extant jawless vertebrates. Relatively soon thereafter, a second duplication round yielded the -1, -2, -3, and -4 paralog types now found in all jawed vertebrates, from sharks to humans. It is possible to assert that these duplication events correlate well to the Ohno hypothesized 2R (two round) vertebrate whole genome duplication (WGD), as refined in more recent treatments. The quadruplication can therefore be placed at approximately 400 Myr ago. Echinoderms, hemichordates, cephalochordates, and urochordates have only a single copy of Teneurin in their genomes. These deuterostomes and non-vertebrate chordates provide the anchor showing that the quadruplication happened at the root of vertebrates. A first footnote must be brought concerning some of the ‘invertebrate’ relatives of vertebrates, among Deuterostomes. A family of genes that encode 7000 aa proteins was derived from, but is distinct from, the Teneurin family. This distinct family arose early in deuterostomes, yet persists today only in hemichordate and cephalochordate genomes. They are named here TRIPs (Teneurin-related immense proteins). As a second of three ‘footnotes’: a limited number of species exist with additional Teneurin gene copies. However, these further duplications of Teneurins occur for paralog types (a, m, or 1–4) only in specific lineages within Arthropods or Vertebrates. All examples are paralog duplications that evidently arose in association with lineage specific WGDs. The increased Teneurin paralog numbers correlate with WGDs known and published in bony fish, Xenopus, plus select Chelicerates lineages and Crustaceans. The third footnote, alluded to above, is that a Teneurin occurs in one unicellular species: Monosiga brevicollis. Teneurins are solely a metazoan, bilaterian-specific family, to the exclusion of the Kingdoms of prokaryotes, plants, fungi, and protists. The single exception occurs among the unicellular, opisthokont, closest relatives of metazoans, the choanoflagellates. There is a Teneurin in Monosiga brevicollis, one species of the two fully sequenced choanoflagellate species. In contrast, outside of triploblast-bilaterians, there are no Teneurins in any diploblast genomes, including even sponges – those metazoans closest to choanoflagellates. Perhaps the ‘birth’ of the original Teneurin occurred in a shared ancestor of M. brevicollis and metazoans, then was lost in M. brevicollis’ sister species, and was serially and repeatedly lost in all diploblast metazoans. Alternatively, and as favored above, it first arose in the ‘urBilaterian,’ then was subsequently acquired from some bilaterian via horizontal transfer by a single choanoflagellate clade. The functional partnership of Teneurins and Latrophilins was discovered in rodents through the LPH1-TENM2 interaction. Recent work extends this to further members of each family. Surveying when the interacting domains of Teneurins and Latrophilins co-exist within different organisms can give an indication of how widespread their functional cooperation might be, across bilaterians. Paralog number for the two families is relatively correlated among bilaterians, and paralog numbers underwent co-increase in the WGDs mentioned above. With co-increasing paralog numbers, the possible combinatorial pairs grow factorially. This should have a significant impact for increasing nervous system complexity. The 3 key events in the ‘natural history’ of the Teneurins and their Latrophilin partners coincide with the ascendance of particularly successful metazoan clades: bilaterians; arthropods; and vertebrates. Perhaps we can attribute some of this success to the unique Teneurin family, and to its partnership with Latrophilins.